1980
DOI: 10.1172/jci109759
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Helper T Cell Function In Vitro by d-Penicillamine and CuSO4

Abstract: A B S T R A C T The effect of D-penicillamine (Pen) and mixtures of Pen and copper sulfate on the capacity of normal human peripheral blood mononuclear cells (PBM) to generate immunoglobulin-secreting cells (ISC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…It may, therefore, be suggested that the observed inhibition by -Pen and cupric ion is expressed through the action of H202 produced by these two agents. This is also consistent with previous findings that H202 suppresses the functions of T (18,22) and natural killer cells (27).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It may, therefore, be suggested that the observed inhibition by -Pen and cupric ion is expressed through the action of H202 produced by these two agents. This is also consistent with previous findings that H202 suppresses the functions of T (18,22) and natural killer cells (27).…”
Section: Resultssupporting
confidence: 94%
“…Although a variety of actions ofthis drug have been reported to be responsible for its therapeutic efficacy (14)(15)(16)(17)(18)(19)(20)(21)(22), the mechanism underlying its beneficial effects has not been adequately explained. To investigate the possible effects of D-Pen on angiogenesis, we have studied the action ofthis drug on basal and endothelial cell growth factor (ECGF)-stimulated proliferation of human umbilical vein EC, and also on ECGF-induced neovascularization in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was observed in isolated T cells incubated with methyldopa and in T cells from patients taking methyldopa. Other studies demonstrating a selective effect on suppressor T-cell function by SLE-inducing drugs have not been reported, although it has been suggested that autoantibody formation induced by D-penicillamine therapy may also be related to suppressor T-cell dysfunction caused by this drug (33).…”
Section: Tmitomentioning
confidence: 99%
“…DP together with copper sulfate or Cp-Cu can inhibit T lymphocyte proliferation in vitro (7). T helper cells appear to be particularly sensitive to inhibition by DP and copper sulfate (17,18), although a recent study suggests that B lymphocytes are more sensitive to H202 than are T celis (19). Natural killer cell function is also inhibited by reactive oxygen species released from activated monocytes and polyrnorphonuclear leukocytes (20).…”
Section: Discussionmentioning
confidence: 99%